International spillovers of quantitative easing - Marcin Kolasa; Grzegorz Wesołowski (European Central Bank (ECB), 2018)
This paper develops a two-country model with asset market segmentation to investigate the effects of quantitative easing implemented by the major central banks on a typical small open economy that follows independent monetary policy. The model is able to replicate the key empirical facts on emerging countries' response to large scale asset purchases conducted abroad, including inflow of capital to local sovereign bond markets and an increase in international comovement of term premia. According to our simulations, quantitative easing abroad boosts domestic demand in the small economy, but undermines its international competitiveness and depresses aggregate output, at least in the short run. This is in contrast to conventional monetary easing in the large economy, which has positive spillovers to output in other countries. We also find that limiting these spillovers might require policies that affect directly international capital flows, like imposing capital controls or mimicking quantitative easing abroad by purchasing local long-term bonds.
Keywords: E44; E52; F41; 330; quantitative easing; international spillovers; bond market segmentation; term premia